PHP and MySQL 24-hour trainer - Tarr, Andrea; Safari eBooks ([S.l.] : Wrox, 2011)
"Assuming no previous experience with PHP or MySQL, this book-and-video package is ideal reading for anyone who wants to go beyond HTML/CSS in order to provide clients with the most dynamic web sites possible. The approachable tone breaks down the basics of programming and PHP and MySQL in individual lessons starting with the installation of the programs necessary to run PHP. You begin with a static web site and then watch and learn as PHP functionality is added as you work through the lessons. When working with databases, the MySQL database is introduced with demonstrations that show how to interact with it. The accompanying videos enhance your learning experience, as each lesson in the book is portrayed in the video exercises."--Resource description page.
Title from title screen.
Author names and date of publication from resource description page (viewed Aug. 29, 2012).
Presenter, Andrea Tarr.
Keywords: MySQL (Electronic resource); Web site development; PHP (Computer program language); Web databases; Database management; Electronic books